Genus Macronemurus costa, 1855 in the northwestern part of the Balkan Peninsula (Neuroptera: Myrmeleontidae) - Devetak, Dušan (Annales. Series historia naturalis, 1997)
Distribution of two ant-lion species, Macronemurus appendiculatus (Latreille) and M. bilineatus Brauer, in the northwestern part of the Balkan Peninsula is described and preliminary analysis of food supply of M. appendiculatus is carried out
Keywords: Balkan; Balkans; favna; Macronemurus; volkec